The problems of the problems of the building a system of indicators for assesing the impact of the economy’s shadowization on the potential of sustainable development of the territory - Viktoriia Boronos; Оlena Shkarupa; Zhanna Kobets (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Економіка, 2019)
The article deals with the forming of indicators characterizing the process of shadowing the economy and its impact on the potential of the sustainable development of the territory, taking into account the financial and economic component. It was determined that the shadowization of the economy directly affects the system of the national economy. The expediency of studying shadow economy as separate indicators in the general dynamics of macroeconomic development, but as integral components of the potential for sustainable development of the territory was justified. The creation of new programs and plans designed to bring the regions to a new level of quality in the development of territories depends on the level of influence of indicators of the shadow economy. The main criteria for assessing the impact of the shadow economy, the potential for sustainable development of the territory in the context of the integration of Ukraine into the European Union and the reform of local government were established. It was determined that efficient realization of the potential for the sustainable development of a territory largely depends on the creation of a system for monitoring the processes of shadow economy. The ways of using the system of indicators and the directions of building a system of indicators for assessing the impact of the economy’s shadowization on the development of the potential for sustainable development of the territory, including financial were identified. One of the problems of using indicators of the economy’s shadowization in managing the potential for the development of territories proved to be its information support, namely, the assessment of the actual state of indicators of shadowization. A scientific and methodological approach to building and assessing the indicators of the formation of components of an indicator of sustainable development of the territory, taking into account the mutual influence of the factors of the economy’s shadowization on the basis of economic and mathematical analysis, which includes six stages with the interpretation of the results, was proposed. The composition of the indicators of the formation of an indicator of sustainable development was suggested to consider taking into account the financial and economic factors of sustainable development of the territory.